Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1108/02621710210426871
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐growth small businesses: learning “architecture”

Abstract: Internationally, a certain market failure has become apparent in terms of the effective engagement of small business owner-managers in business support programs, and in the wider concept of life long learning. There exists a cultural gap between support agencies and the small business sector's perceptions of the utility of formal support and learning interventions to the business performance of their business. Therefore, this paper extends knowledge and understanding within this context relative to what consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
(28 reference statements)
1
39
0
4
Order By: Relevance
“…These ongoing developments are very much to be welcomed, and we can now talk with some confidence about the need to recognise the distinguishing features of the 'learning architecture' (Jenlink, 1994;Morrison and Bergin-Seers, 2002) of small firms. Specifically, we can highlight the scarcity of dedicated training functions in small businesses, their very limited resources, a need for training that meets immediate requirements, and the central role played by informal and networked learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ongoing developments are very much to be welcomed, and we can now talk with some confidence about the need to recognise the distinguishing features of the 'learning architecture' (Jenlink, 1994;Morrison and Bergin-Seers, 2002) of small firms. Specifically, we can highlight the scarcity of dedicated training functions in small businesses, their very limited resources, a need for training that meets immediate requirements, and the central role played by informal and networked learning.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is ultimately argued, while a highly structured, formalised and bureaucratic approach to skill development is likely to be inappropriate for most small firms, this should not be equated with the rejection of formal training as a legitimate method of learning. A more balanced and nuanced analysis should instead be adopted; one that acknowledges the heightened importance of an informal 'learning architecture' (Jenlink 1994;Morrison and Bergin-Seers 2002) among small businesses, but also accepts that formal training potentially has much to offer within that architecture -particularly if presented, delivered and targeted in appropriate ways.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the study by Lans et al (2004) suggested that non-formal and informal learning seem to play an especially important role in the competence development of entrepreneurs. Similarly, Morrison and Bergin-Seers (2002) report that the owner-managers in their sample expressed a disinclination to participate in formal learning programmes, and exhibited a disposition towards learning in a practical and experiential way, mainly through informal mediums, with the preferred model being networks. Boekaerts and Minneart (1999, p.536) outline a number of attributes of informal learning, which link self-regulated learning to the informal learning context, and as such, are important considerations in the present investigation:…”
Section: Self-regulated Learning and Informal Learning Contextsmentioning
confidence: 99%
“…In the same vein, it is desirable that the leader of growing SMEs be accompanied by a mentor. Indeed, his learning would be facilitated by a mentor who would be able to transform his own knowledge and make it compatible with those of the novice entrepreneur (Morrison and Bergin-Seers, 2002). Mentoring is also very relevant in the context of personal development of small business leader (Hudson-Davies et al, 2002); the mentor can play a positive role model, inspiring the novice entrepreneur to continue seeking for excellence (Lockwood et al, 2002).…”
Section: Mentoringmentioning
confidence: 99%